Synthesis of poly (Diallyldimethylammonium Chloride) coated iron oxide for the degradation of e. Coli via fenton-like degradation - Ong, Sin Hui (2023)
Waterborne infections are responsible for millions of deaths annually, highlighting the crucial need for effective water treatment processes to ensure public health. Consumption of contaminated water can cause severe microbial infections, leading to significant health concerns such as damage to the intestinal lining and even fatalities. Conventional techniques such as chlorination may result in incomplete removal of pathogenic E. coli, necessitating the exploration of alternative methods. Thus, removal of E. coli by Fenton-like degradation using poly(diallyldimethylammonium chloride) coated iron oxide, PDDA/Fe3O4 was investigated in this study. PDDA/Fe3O4 was synthesized using co-precipitation method and was characterized using Fourier transformed infrared spectroscopy (FTIR), scanning electron microscopy coupled with energy dispersive X-ray (SEM-EDX), Brunauer-Emmett-Teller method (BET), thermogravimetric analysis (TGA), X-ray diffraction (XRD) and pH drift. The feasibility of PDDA/Fe3O4 in the degradation of E. coli was also studied. The focus process parameters studied were PDDA/Fe3O4 dosage (30 mg and 50 mg) and H2O2 concentration (0 mmol/L and 4 mmol/L). In the presence of H2O2, 30 mg of PDDA/Fe3O4 was found to be sufficient to fully degrade E. coli present in water sample through Fenton-like degradation. In the absence of H2O2, 50 mg of PDDA/Fe3O4 was sufficient to fully remove E. coli present in the water sample through adsorption process. It could be concluded that Fenton-like degradation using PDDA/Fe3O4 could be a viable alternative for removing E. coli in the water treatment process.